Research on magnetic-fluid-thermal-stress multi-field bidirectional coupling of high speed permanent magnet synchronous motors - Yongming Xu; Ziyi Xu; Huan Wang; Wenhui Liu (Case Studies in Thermal Engineering, 2024)
Due to the fact that high speed permanent magnet synchronous motors (HSPMSM) are direct drives instead of using gears, they have technical and economical advantages in many applications. In this paper, a 150 kW, 30,000 r/min HSPMSM was used as research object, for which a magnetic-fluid-thermal-stress multi-field coupling model was developed and solved. Motor losses were obtained from electromagnetic analysis and were applied as heat source. Subsequently, the temperature and fluid distribution were solved according to given heat source characteristics and cooling structure. Based on this, the rotor stress distribution influenced by the temperature load was further obtained. On the other hand, the effect of temperature change on conductor resistivity, permanent magnet remanence, cooling medium thermophysical properties, and loss characteristics, which in turn affect temperature and stress distribution, was considered. The bidirectional coupling of multi-fields was achieved by iterative calculations in the ''forward'' and ''reverse'' cycles. The results showed that the hotspot temperature increased by 14.19 % and the tangential stress in permanent magnet increased by 5.28 % compared to the unidirectional coupling. Finally, an experiment platform was built, and tests were conducted. The results showed that the temperature obtained by bidirectional coupling was closer to the experimental result.